Feasibility Study for Reuse of Zarand Thermal Power Plant Wastewater Passed through Reverse Osmosis Process - Elham Rahmanpour Salmani; Alireza Ghaderi; Seyed Ahmad Ataei; Maryam Dolatabadi (Iranian Journal of Health, Safety and Environment, 2017)
Increased urbanization and industrialization have disturbed the balance between water demand and water supply. Thermal power plants are among the largest water consumers and wastewater producers, while wastewater reuse can deal with the both concerns. Effluents of thermal power plants contain various pollutants, so remediation is needed before any other usage. Assessment the efficacy of Reverse Osmosis (RO) system in treatment of Zarand power plant wastewater for reuse was the aim of present work. Physical and chemical parameters including pH, temperature, turbidity, BOD, COD, chromium, sulphate, chloride, nitrate, and phosphate ions were determined in samples collected from three locations of power station: feed water, influent to RO, and effluent. Sampling was done in the first six months of 2012. Data was characterized using descriptive statistics and Excel software. The average performance of RO in the removal percent of turbidity, BOD, COD, chromium, sulphate, chloride, nitrate, and phosphate was 57.5, 14.5, 27.4, 28, 46, 26, 73, and 99% respectively. In spite of less satisfying values of efficiency, mean values of pH, turbidity, BOD, COD, chromium, chloride, nitrate, and phosphate measured in effluent passing through RO were 7.5, 0.14 NTU, 1.8, 2.83, 0.018, 320, 1.6, and 0.001 mg/l respectively, all in compliance with discharging or irrigation standards, while 704 mg/l of sulphate ions detected in effluent, were much higher than acceptable limits.